Confirmatory factor analysis of Bosnian version of Behavior Rating I nventory of executive functions in children with intellectual disability - Protić, Mladen; Válková, Hana (Journal of Exceptional People, 2019)
The purpose of the study was to assess factor structure of Bosnian version of Behaviour Rating Inventory of Executive Function (BRIEF). This instrument is a rating scale used for assessment of executive functions in children and adults of diff erent ages and sample category. Executive functions are crucial for early development of cognitive and social capacities, which are very important for children with intellectual disabilities and very often serve as a basis of their future integration into society. However, benefi ts of well-developed executive functions, its relationships and eff ects to diff erent aspects of life in this population, have started to be investigated relatively recently. Therefore, beside increasing knowledge about executive functions in children with intellectual dis ability, the study aimed to test feasibility and stability of BRIEF in this population with future goal of its application in schools for development of educational plans for children of this population. The sample consisted of 104 children with intellectual disability (62 boys and 42 girls) from 7 to 18 years of age. There were 49 children with mild and 55 with moderate intellectual disability. The BRIEF – teacher version was completed by 15 special education teachers of children participating in the study. The goal was to examine factor struc ture of 8 BRIEF scales: inhibit, shift , emotional control, initiate, working memory, organization of materials, plan/organize and monitor. Teachers were not considered to be participants, but only supporters of its implementation. The study confi rmed original two factor structure of the BRIEF with 80.6 % of total variance explained. It has shown that BRIEF is feasible and reliable in application with this population and it can be used for school assessment as a basis for educational planning and development of executive functions.
Keywords: Bosna a Hercegovina; Statistics as Topic; Behaviour Rating Inventory of Executive Function; Executive Function; průzkumy a dotazníky; Female; dítě; statistika jako téma; ženské pohlaví; Surveys and Questionnaires; Adolescent; lidé; Bosnia and Herzegovina; faktorová analýza statistická; Intellectual Disability; Humans; Male; Child; mužské pohlaví; exekutivní funkce; mentální retardace; Factor Analysis, Statistical; mladiství; chování dětí; Child Behavior